Soft tissue expansion before vertical ridge augmentation: Inflatable silicone balloons or self-filling osmotic tissue expanders? - Prasad Vijayrao Dhadse; Ramareddy Krishnarao Yeltiwar; Manohar Laxmanrao Bhongade; Sunil Dattuji Pendor (Wolters Kluwer Medknow Publications, 2014)
Recent advances in periodontal plastic surgical procedures allow the clinician to reconstruct deficient alveolar ridges in more predictable ways than previously possible. Placement of implant/s in resorbed ridges poses numerous challenges to the clinician for successful esthetic and functional rehabilitation. The reconstruction frequently utilizes one or combination of periodontal plastic surgical procedures in conjunction with autogenous bone grafting, allogenic bone block grafting, ridge split techniques, distraction osteogenesis, or guided bone regeneration (GBR) for most predictable outcomes. Current surgical modalities used in reconstruction of alveolar ridge (horizontal and/or vertical component) often involve the need of flap transfer. Moreover, there is compromise in tissue integrity and color match owing to different surgical site and the tissue utilized is insufficient in quantity leading to post surgical graft exposition and/or loss of grafted bone. Soft tissue expansion (STE) by implantation of inflatable silicone balloon or self filling osmotic tissue expanders before reconstructive surgery can overcome these disadvantages and certainly holds a promise for effective method for generation of soft tissue thereby achieving predictable augmentation of deficient alveolar ridges for the implant success. This article focuses and compares these distinct tissue expanders for their clinical efficacy of achieving excess tissue that predominantly seems to be prerequisite for ridge augmentation which can be reasonably followed by successful placement of endosseous fixtures.